2007
DOI: 10.1142/s0219633607003040
|View full text |Cite
|
Sign up to set email alerts
|

Computational Insights on the Lone Pair Induced Barrier Modulation in the Thermal Rearrangement of 6-Halo-2-Pyrones

Abstract: 2-pyrones undergo intramolecular thermal rearrangement resulting in the migration of groups at 3-position to 5-position and vice-versa. Rearrangement of 6-halopyrone is a tandem process involving electrocyclic ring opening and closure (ERO & ERC), rotation, sigmatropic shift. It has been modeled at MP2/6-31g (d) level to understand the migratory aptitude of the halogens. Computations show that electrocyclic transition state and the corresponding intermediate which could not be located in 2-pyrone rearrangement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…We [29][30] have studied the thermolysis of 2-pyrone and 6-halo-2-pyrone and have found that fluorine substitution substantially altered the potential energy surface for ERO, sigmatropic rearrangement and electrocyclic ring closing (ERC) of pyrones. Fluorine is known to strongly perturb reaction barriers and mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…We [29][30] have studied the thermolysis of 2-pyrone and 6-halo-2-pyrone and have found that fluorine substitution substantially altered the potential energy surface for ERO, sigmatropic rearrangement and electrocyclic ring closing (ERC) of pyrones. Fluorine is known to strongly perturb reaction barriers and mechanisms.…”
Section: Introductionmentioning
confidence: 99%